Oxcarbazepine Adjunctive Therapy for Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The safety and efficacy of oxcarbazepine (OXC) as adjunctive therapy for refractory partial seizures were evaluated in 267 patients in a multicenter (47 centers in 8 countries; Argentina, Chile, Uruguay, Australia, New Zealand, Canada, Israel, and the USA), randomized, placebo-controlled trial, and reported from the Children's Hospital, Cincinnati, OH.